How Networking Empirically Influences the Types of Innovation?: Pardis Technology Park as a Case Study - Amir Mirzadeh Phirouzabadi; M Mahmoudian; M Asghari (Computer Engineering and Applications Journal, 2013)
Nowadays, Innovation can be named as one of the best practices as quality, speed, dependability, flexibility and cost which it helps organization enter to new markets, increase the existing market share and provide it with a competitive edge. In addition, organizations have moved forward from â€œhiding idea (Closed Innovation)â€ to â€œopening them (Open Innovation)â€. Therefore, concepts such as â€œopen innovationâ€ and â€œinnovation networkâ€ have become important and beneficial to both academic and market society. Therefore, this study tried to empirically study the effects of networking on innovations. In this regard, in order to empirically explore how networking influences innovations, this paper used types of innovations based on OCED definition as organizational, marketing, process and product and compared their changes before and after networking of 45 companies in the network Pardis Technology Park as a case study. The results and findings showed that all of the innovation types were increased after jointing the companies to the network. In fact, we arranged these changing proportions from the most to the least change as marketing, process, organizational and product innovation respectively. Although there were some negative growth in some measures of these innovations after jointing into the network.